PENGARUH FLYPAPER EFFECT TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA UTARA (STUDI KOMPARASI PEMERINTAH KOTA DENGAN KABUPATEN) - purba, kezia Aranthxa; Susilo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Flypaper Effect is a situation where the expenditure of a region tends to be more responsive to transfer funds than its own regional income. The purpose of the study is to examine and analyze the flypaper effect, and to determine whether regional expenditure can act as a mediating variable between income and economic growth. By conducting a comparative study between cities and regencies in North Sumatra Province in 2011-2019, by applying path analysis. The results of the study show that in these cities and regencies there was a flypaper effect and regional expenditure was unable to mediate own regional income to economic growth. Therefore, to achieve fiscal autonomy and financial independence, it is necessary to minimize the flypaper effect and determine the allocation of regional expenditure effectively.